Women Entrepreneurs in Indonesia : A Pathway to Increasing Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2016)
The world today believes that supporting women entrepreneurs is vital for economic growth. As economic opportunities increase, unprecedented numbers of women are entering the world of business and entrepreneurship. The number of women entrepreneurs has risen in global economy including in developing countries. However, the majority of women entrepreneurs in developing countries are still operating in small and micro enterprises with very little growth. Most women entrepreneurs run businesses in the informal and traditional female sectors. There is still prevalence of gender gaps in critical skills to run successful businesses. While education for women is making major progress along the years, women often still lack vocational and technical skills, as well as work experience to enable them to run large businesses. Women are also reported to be less likely to have access to information and communications technology (ICT) which plays a significant role in the highly integrated global market. The other constraint, that is major, is the lack of finance. This study aims to understand the specific characteristics, challenges, and opportunities of women entrepreneurs in Indonesia. By understanding the real condition of women micro-entrepreneurs in Indonesia, it is expected to be able to define the right policy recommendation and supports to promote the women entrepreneurs. To be different to other existing study on MSMEs and women entrepreneurs, this study investigate the large number of women entrepreneurs in Indonesia across provinces that cover java and non-java regions. In addition, the study also shifts the focus from poverty reduction to a growth imperative.